Economic reform, urban proximity and small town development in China: a tale of two towns - Liu, Kai (2008)
This thesis studies small town development in contemporary China (1978-present). It focuses on the socioeconomic impact of economic reform on small town development, with particular emphasis on how gradually released market forces enable urban proximity to play different roles to determine the developmental trajectory of small towns. The research design chooses two economically prosperous towns with different degrees of urban proximity, in which fieldwork is conducted. Xihongmen town is located in suburban Beijing and Zhulin town is located in a rural area of Henan province. The research focuses on government, firms and people as three key elements of small town development, and systematic comparisons have been used as the key research strategy throughout.